Perencanaan Pompa Hidram Untuk Irigasi Di Kabupaten Lamongan - Dayat Indri Yuliastuti; Brian Adika Sugiharto; Muhammad Lawdy Dhiyaa Vansya; Sekar Ayu Kuncaravita; Rizki Astri Apriliani (Universitas Muhammadiyah Surabaya, 2026)
The availability of irrigation water is a crucial factor in supporting agricultural productivity, especially in areas that have elevation differences between water sources and paddy fields. Daliwangun village in Sugio subdistrict, Lamongan regency, faces water distribution problems because the location of the rice fields is at a higher elevation than Gondang Reservoir as the main source of surface water. This study aims to plan an irrigation system using a hydram pump that is able to drain water without electrical energy or fuel. Research methods include topographic analysis, calculation of the main reservoir discharge, irrigation water requirements based on rice–rice–crops planting patterns, as well as analysis of hydram pump capacity based on head fall and head lift. The results showed that the elevation of rice fields is at 46-57 m, while the elevation of the reservoir is at 25-30 m, with an elevation difference of 15-25 m so that gravity flow is not possible. The mainstay discharge of the reservoir is sufficient for basic needs, but a pumping system is required to overcome the height. Calculation of hydram pump capacity shows that the system can meet the needs of irrigation on an area of 23-25 ha with the planned pump configuration. In conclusion, the hydram pump is feasible as a sustainable irrigation solution in Daliwangun Village.